2005
DOI: 10.1007/s10812-006-0012-5
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic defects in ZnO and GaN crystals

Abstract: The kinetics of defect formation in the system of a crystal with a nonmetal component in the activated gas phase has been investigated. The data obtained has made it possible to develop physicochemical methods of regulating the defect-formation processes depending on the adsorption-desorption-crystallization equilibrium on the surface of a crystal. A kinetic model of defect formation in the A II B VI and A III B V compounds is proposed. Results of the kinetic analysis of the intrinsic defects in the ZnO and Ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…Earlier, we showed in [26] that the band at 370.2 nm in ZnO is caused by the recombination of excitons at the neutral acceptor of zinc vacancy, and 402 nm is associated with radiative transitions in the conduction band or the acceptor, where there is intrinsic defect of the zinc vacancy V Zn with a depth of~0.3 eV above the ceiling of the valence band. We also showed in [27] that the concentration of zinc vacancies, depending on the conditions of heat treatment, can be 10 17 to 10 19 cm −3 . This is supported by the data of [28], wherein the authors also associated the observed band of 401 nm with a zinc vacancy.…”
Section: Samplementioning
confidence: 60%
“…Earlier, we showed in [26] that the band at 370.2 nm in ZnO is caused by the recombination of excitons at the neutral acceptor of zinc vacancy, and 402 nm is associated with radiative transitions in the conduction band or the acceptor, where there is intrinsic defect of the zinc vacancy V Zn with a depth of~0.3 eV above the ceiling of the valence band. We also showed in [27] that the concentration of zinc vacancies, depending on the conditions of heat treatment, can be 10 17 to 10 19 cm −3 . This is supported by the data of [28], wherein the authors also associated the observed band of 401 nm with a zinc vacancy.…”
Section: Samplementioning
confidence: 60%
“…Binary semiconductors can be realized from wide to low band gap (ZnO to HgTe). However very often the compounds show intrinsic defects [2,3] or indirect band gaps [4], which makes a search for new semiconducting compounds necessary. However ternary semiconductors were not investigated systematically up to date.…”
Section: Introductionmentioning
confidence: 99%